Development of History of Islamic Culture: Learning Media Based on “Siraa” Android Applications - Laila Ngindana Zulfa; Prawidya Lestari; Riyadi Sollikhin; Waedoloh, Husen (Jurnal Pendidikan Islam Indonesia, 2024)
The development of science and technology required the education sector to strive for innovation and transformation. One of these efforts was to develop learning media, because learning media can be a means of improving the quality of education and achieving educational goals. This research aimed to determine the need for the development of an Android application-based history of Islamic culture through learning media on the history of Khulafaur Rasyidin material at MA Darul Ulum. This research was development research, or research and development (R&D). This research used the Borg and Gall development model, which is modified for the sixth stage, namely, limited product testing. This media development's results were valid for use in the very good category. Based on the results of the feasibility analysis carried out by material experts, who got a score of 82%, and media experts, who got a score of 94%, although this research made a significant contribution to the development of the history of Islamic culture, learning media. Therefore, it necessary to refine it up to the dissemination stage to all MA’s in Indonesia.